Plan estratégico para el mejoramiento de servicios de la empresa municipal de vivienda y legalización de terrenos del GAD municipal de el cantón Valencia periodo 2015-2021 - Morales Loor, Luisa María (2016)
This research called STRATEGIC PLAN TO IMPROVE MUNICIPAL SERVICES COMPANY OF HOUSING AND AUTHENTICATION OF LAND OF VALENCIA GAD CANTON CITY PERIOD 2015- 2019, he was held at the Valencia Canton, by the need to know whether the Commission has adequate plan strategy that could improve the services provided to the population of the Canton. The overall objective of this project is to develop a strategic plan to improve services EMVI EP Valencia, as well as the implementation of that plan this year and help the company provide better service to the community. The present is all the literature on strategic planning concepts, strategic plans, reviewing the most relevant aspects and summarizing phases thereof. For this type Library Research Documentary descriptive supported with data collection methods like Interview, Survey that applied both to staff working in the company and the beneficiaries of it was used. The sources of data collection were both primary and secondary the tabulation and analysis of them which allowed us to draw conclusions and recommendations; on this basis develop our proposal is nothing more than the strategic plan that was implemented in the institution. After analyzing the data concluded that the company did not have an adequate strategic planning, so it is possible to design our strategic plan, which after being analyzed by the directors of the same it will launch and thus ensure that the housing company its services to the community. Keywords: Strategic Plan, Continuous improvement, housing company.